2016
DOI: 10.1007/s11419-016-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-drug interactions and masking effects in sport doping: influence of miconazole administration on the urinary concentrations of endogenous anabolic steroids

Abstract: We have investigated the influence of oral\ud miconazole administration on the urinary concentrations of\ud endogenous anabolic androgenic steroids of doping relevance,\ud specifically considering all these compounds routinely monitored in doping control analysis, in the framework of the\ud steroidalmodule of the ‘‘athlete biologicalpassport’’, and other\ud steroids, including dehydroepiandrosterone, 5a-dihydrotestosterone, and the hydroxylated metabolites recently\ud proposed as additional markers of the inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…The steroid profile parameters monitored in ABP were determined following the procedure routinely used, and under the WADA and ISO17025 accreditation of our laboratory (Laboratorio Antidoping FMSI of Rome, Italy). The trimethylsilyl derivatives of the endogenous steroids in free plus glucuronated fraction in urine were measured …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steroid profile parameters monitored in ABP were determined following the procedure routinely used, and under the WADA and ISO17025 accreditation of our laboratory (Laboratorio Antidoping FMSI of Rome, Italy). The trimethylsilyl derivatives of the endogenous steroids in free plus glucuronated fraction in urine were measured …”
Section: Methodsmentioning
confidence: 99%
“…The data acquisition was performed in multiple reaction monitoring mode. This already published method is used for the determination of the steroid profile as defined in the WADA technical document TD2018EAAS, used routinely by the WADA accredited laboratory of Rome and under the ISO17025 scope of the same laboratory. The steroid profile included the quantitation of T, E, A, Etio, 5αAdiol and 5βAdiol, and the ratios T/E, A/Etio, A/T, 5αAdiol/5βAdiol and 5αAdiol/E.…”
Section: Methodsmentioning
confidence: 99%
“…According to WADA guidelines, the presence of dutasteride in urine samples collected during doping control tests has to be checked. For this reason, the possibility of including dutasteride in the analytical procedures (mainly based on the use of liquid/liquid extraction at controlled pH using TBME, or on the use of cation exchange cartridges) already in use in our WADA‐accredited laboratory was considered . In detail, the extraction protocol currently adopted by our laboratory to screen for more than 300 prohibited compounds by LC–MS was selected.…”
Section: Methodsmentioning
confidence: 99%
“…The urine samples utilized in this study were from previous research carried out in our laboratory . [The administration studies were approved by the Local Ethical Committee (approval code: Prot.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, by in vitro experiments carried out on human liver microsomes (HLM) and single CYP or uridine 5′‐diphospho‐glucuronosyl‐transferase (UGT) isoforms, we observed that the metabolic profile of other compounds included in the WADA prohibited list (ie, toremifene, stanozolol and 19‐nortestosterone) was extensively altered in the presence of both antifungals and antidepressants …”
Section: Introductionmentioning
confidence: 99%